Interactions among Return and Market Capitalization of Bitcoin and Turkish lira - Zreba, Mohamed Abdulfattah I (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
The aim of this thesis is to distinguish the interactions between return and market capitalization of Bitcoin and Turkish lira, a quantitative study was conducted out. In order to conduct the study, the daily returns and market capitalization of Bitcoin and Turkish Lira were used for the timespan of May 31, 2019, to May 29, 2021. The thesis goal was accomplished using several methods. Initially, applying descriptive statistics to find out whether the data series are normally distributed or not. Second, unit root tests were applied to test the integration order and observe whether the variables are stationary or not, in addition to determining if the data have constant covariance or rather variance over time. Lastly, the recently discovered Granger causality in quantiles approach by Troster (2018) was applied. Furthermore, the findings demonstrate that Returns of Bitcoin have a significant impact on the Turkish lira and vice versa, indicating the cryptocurrency's predictive power over the exchange rate of the Turkish lira. As a recommendation, the returns of cryptocurrencies should be closely monitored by investors who actively trade on the Turkish exchange market. Moreover, investors can follow the market capitalization of Bitcoin so they can have some ideas about returns of bitcoin for their investment decision.

ÖZ: Bu çalışmanın amacı Bitcoin ve Türk lirasının getiri ve piyasa değerleri arasındaki etkileşimin ampirik bir çalışma ile incelenmesidir. Çalışmanın gerçekleştirilebilmesi için 31 Mayıs 2019 ile 29 Mayıs 2021 dönemini kapsayan değişkenlerin günlük verileri kullanılmıştır. İlk olarak, değişkenlerin normal dağılıp dağılmadığına bakılmış, ardından birim kök testleri uygulanarak değişkenlerin durağan olup olmadıkları incelenmiştir. Son olarak ise Troster (2018) tarafından geliştirilen Granger Kantil Nedensellik testi ile Bitcoin ve Türk lirası getiri ve piyasa değerleri arasındaki etkileşim incelenmiştir. Elde edilen sonuçlara göre Bitcoin getirilerinin Türk lirası üzerinde ve Türk lirası getirilerinin Bitcoin üzerinde anlamlı bir ilişkisi olduğu sonucuna varılmıştır. Bu sonuçlara göre kripto para biriminin Türk lirası döviz kuru üzerinde önemli bir tahmin gücü olduğu gözlemlenmiştir. Dolayısıyla, kripto para birimi getirilerinin ve piyasa değerinin aktif olarak Türk lirasına yatırım yapan yatırımcılar tarafından dikkate alınması önerilmektedir.
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2022. Supervisor: Assist. Prof. Dr. Nigar Taşpınar.
Keywords: Banking and Finance Department; Cryptocurrency--Bitcoin--Turkish Lira; Cryptocurrency, Returns of Bitcoin, Market Capitalization, Turkish Lira, Granger Causality in Quantiles